Red regional para América latina y el Caribe: Informe de la Primera Reunión Regional del Programa International de Evaluación de Musa, 10-11 Marzo 1993, La Lima, Honduras - International Network for the Improvement of Banana and Plantain (1994)
Synthesis of the work carried out from 1990 to 1992. The most important research activities were: a) genetic improvement, b) germplasm exchange, c) classification of germplasm, d) evaluation of germplasm, e) tissue culture, f) plantain farming system, g) study on the microbiology of banana and plantain plantation soils, h) research by institutes associated with the network. The document also contains a summary of the work carried out by the regional information and documentation network. Strategy of the network for the five years to come and an INIBAP-LAC research programme proposal (1994-1998) are also included.